CAPÍTULO II: MARCO DE REFERENCIA - Naranjo Rojas, Anisbed; Estrada González, Catalina; Cruz Mosquera, Freiser Eceomo (Universidad Santiago de Cali, 2025)
Home care is a health care service that provides continuous assistance to patients with health problems who, due to the characteristics of their illness, do not require hospitalization in a conventional center. From the perspective of other authors, it is defined as the modality of programmed assistance that brings biopsychosocial and spiritual care and attention to the patient's home.